Ultrasound-Enhanced Chemiluminescence for Bioimaging - Le, Duong; Dhamecha, Dinesh; Gonsalves, Andrea; Menon, Jyothi U. (Frontiers in Bioengineering and Biotechnology, 2020)
Tissue imaging has emerged as an important aspect of theragnosis. It is essential not only to evaluate the degree of the disease and thus provide appropriate treatments, but also to monitor the delivery of administered drugs and the subsequent recovery of target tissues. Several techniques including magnetic resonance imaging (MRI), computational tomography (CT), acoustic tomography (AT), biofluorescence (BF) and chemiluminescence (CL), have been developed to reconstruct three-dimensional images of tissues. While imaging has been achieved with adequate spatial resolution for shallow depths, challenges still remain for imaging deep tissues. Energy loss is usually observed when using a magnetic field or traditional ultrasound (US), which leads to a need for more powerful energy input. This may subsequently result in tissue damage. CT requires exposure to radiation, and a high dose of contrast agent to be administered for imaging. The BF technique, meanwhile, is affected by strong scattering of light and autofluorescence of tissues. The CL is a more selective and sensitive method as stable luminophores are produced from physiochemical reactions, e.g. with reactive oxygen species (ROS). Development of near infrared-emitting luminophores also bring potential for application of CL in deep tissues and whole animal studies. However, traditional CL imaging requires an enhancer to increase the intensity of low-level light emissions, while reducing the scattering of emitted light through turbid tissue environment. There has been interest in the use of focused ultrasound (FUS), which can allow acoustic waves to propagate within tissues and modulate chemiluminescence signals. While light scattering is decreased, the spatial resolution is increased with the assistance of US. In this review, chemiluminescence detection in deep tissues with assistance of FUS will be highlighted to discuss its potential in deep tissue imaging.